Premature mortality in autism spectrum disorder - Hirvikoski, Tatja; Bölte, Sven (The British journal of psychiatry, 2016)
Background - Mortality has been suggested to be increased in autism spectrum disorder - (ASD). Aims - To examine both all-cause and cause-specific mortality in ASD, as well as - investigate moderating role of gender and intellectual ability. Method - Odds ratios (ORs) were calculated for a population-based cohort of ASD - probands (n = 27 122, diagnosed between 1987 and 2009) - compared with gender-, age- and county of residence-matched controls - (n = 2 672 185). Results - During the observed period, 24 358 (0.91%) individuals in the general - population died, whereas the corresponding figure for individuals with - ASD was 706 (2.60%; OR = 2.56; 95% CI 2.38-2.76). Cause-specific analyses - showed elevated mortality in ASD for almost all analysed diagnostic - categories. Mortality and patterns for cause-specific mortality were - partly moderated by gender and general intellectual ability. Conclusions - Premature mortality was markedly increased in ASD owing to a multitude of - medical conditions.
Gesehen am 24.10.2019